The botanical origin and antioxidant, anti-BACE1 and antiproliferative properties of bee pollen from different regions of South Korea - Yuchi Zou; Jian Hu; Wenting Huang; Liyun Zhu; Mingjie Shao; Confidence Dordoe; Young-Joon Ahn; Dongxue Wang; Yeli Zhao; Ye Xiong; Xue Wang (BMC, 2020)
Abstract Background Bee pollen (BP) has been used as a traditional medicine and food diet additive due to its nutritional and biological properties. The potential biological properties of bee pollen vary greatly with the botanical and geographical origin of the pollen grains. This study was conducted to characterize the botanical origin and assess the antioxidant effects of ethanol extracts of 18 different bee pollen (EBP) samples from 16 locations in South Korea and their inhibitory activities on human β-amyloid precursor cleavage enzyme (BACE1), acetylcholinesterase (AChE), human intestinal bacteria, and 5 cancer cell lines. Methods The botanical origin and classification of each BP sample was evaluated using palynological analysis by observing microscope slides. We measured the biological properties, including antioxidant capacity, inhibitory activities against human BACE1, and AChE, and antiproliferative activities toward five cancer cell lines, of the 18 EBPs. In addition, the growth inhibitory activities on four harmful intestinal bacteria, six lactic acid-producing bacteria, two nonpathogenic bacteria, and an acidulating bacterium were also assessed. Results Four samples (BP3, BP4, BP13 and BP15) were found to be monofloral and presented four dominant pollen types: Quercus palustris, Actinidia arguta, Robinia pseudoacacia, and Amygdalus persica. One sample (BP12) was found to be bifloral, and the remaining samples were considered to be heterofloral. Sixteen samples showed potent antioxidant activities with EC50 from 292.0 to 673.9 μg mL− 1. Fourteen samples presented potent inhibitory activity against human BACE1 with EC50 from 236.0 to 881.1 μg mL− 1. All samples showed antiproliferative activity toward the cancer cell lines PC-3, MCF-7, A549, NCI-H727 and AGS with IC50 from 2.7 to 14.4 mg mL− 1, 0.9 to 12.7 mg mL− 1, 5.0 to > 25 mg mL− 1, 2.7 to 17.7 mg mL− 1, and 2.4 to 8.7 mg mL− 1, respectively. In addition, total phenol and flavonoid contents had no direct correlation with antioxidant, anti-human BACE1, or antiproliferative activities. Conclusion Fundamentally, Korean bee pollen-derived preparations could be considered a nutritional addition to food to prevent various diseases related to free radicals, neurodegenerative problems, and cancers. The botanical and geographical origins of pollen grains could help to establish quality control standards for bee pollen consumption and industrial production.